2018
DOI: 10.1128/mbio.00819-18
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 Phosphorylation Coordinates the Anti-HIV-1 Response by Diverse Interferons and Tyrosine Kinase Inhibition

Abstract: Macrophages are susceptible to human immunodeficiency virus type 1 (HIV-1) infection despite abundant expression of antiviral proteins. Perhaps the most important antiviral protein is the restriction factor sterile alpha motif domain and histidine/aspartic acid domain-containing protein 1 (SAMHD1). We investigated the role of SAMHD1 and its phospho-dependent regulation in the context of HIV-1 infection in primary human monocyte-derived macrophages and the ability of various interferons (IFNs) and pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…In addition, SAMHD1 function is inhibited by phosphorylation, a process controlled by cyclin-dependent kinases (CDK) and therefore tightly regulated during cell cycle progression [13][14][15]. Different pharmacological agents have been shown to block SAMHD1 phosphorylation, inducing SAMHD1 function and viral restriction [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SAMHD1 function is inhibited by phosphorylation, a process controlled by cyclin-dependent kinases (CDK) and therefore tightly regulated during cell cycle progression [13][14][15]. Different pharmacological agents have been shown to block SAMHD1 phosphorylation, inducing SAMHD1 function and viral restriction [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, immediately before submission of this manuscript another group reported that Type-I, II and III interferon can induce SAMHD1 dephosphorylation (Szaniawski et al, 2018). In principle, each of these signaling pathways could be activated as a consequence of infection by retroviruses or DNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 activation stimulates production of interferons (IFN). In order to understand if IFN plays role in SAMHD1 activation/dephosphorylation after TLR4 activation as recently published 16, 22 , we used the JAK1/2 inhibitor Ruxolitinib (RUXO) that inhibits IFN signalling (Fig.1C) 23 . The inhibitor of IFN signalling could not restore infection and failed to reverse SAMHD1 phosphorylation at T592, suggesting that regulation of SAMHD1 phosphorylation is largely independent of IFN (Fig.1F).…”
Section: Resultsmentioning
confidence: 99%
“…We show here that human primary macrophages exit the cell cycle after exposure to exogenous IFNÎČ) and that this effect is dependent on JAK/STAT signalling. It has been shown that SAMHD1 can be activated/dephosphorylated by type I,II and III IFN 16, 22 in macrophages. We confirmed this observation and showed that SAMHD1 phosphorylation and HIV-1 infection can be rescued when JAK/STAT signalling is blocked after addition of exogenous IFNÎČ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation